Anatomic Nuances of the Ophthalmic Artery Origin from a Ventral Viewpoint: Considerations and Implications for Endoscopic Endonasal Surgery. Issue 4 (31st July 2018) - Naudy, Cristian A; Yanez-Siller, Juan C; Mesquita Filho, Paulo M; Gomez G., Matias; Otto, Bradley A; Carrau, Ricardo L; Prevedello, Daniel M
Abstract: BACKGROUND: The origin of the ophthalmic artery is within the surgical field of endoscopic endonasal approaches (EEAs) to the suprasellar and parasellar regions. However, its anatomy from the endoscopic point-of-view has not been adequately elucidated. OBJECTIVE: To highlight the anatomy of the ophthalmic artery origin from an endoscopic endonasal perspective. METHODS: The origin of the ophthalmic artery was studied bilaterally under endoscopic visualization, after performing transplanum/transtubercular EEAs in 17 cadaveric specimens (34 arteries). Anatomic relationships relevant to surgery were evaluated. To complement the cadaveric findings, the ophthalmic artery origin was reviewed in 200 "normal" angiographic studies. RESULTS: On the right side, 70.6% of ophthalmic arteries emerged from the superior aspect, while 17.6% and 11.8% emerged from the superomedial and superolateral aspects of the intradural internal carotid artery, respectively. On the left, 76.5%, 17.6%, and 5.9% of ophthalmic arteries emerged from the superior, superomedial, and superolateral aspects of the internal carotid, respectively. Similar findings were observed on angiography. All ophthalmic arteries emerged at the level of the medial opticocarotid recess. Overall, 47%, 26.5%, and 26.5% of ophthalmic arteries (right and left) were inferolateral, inferior, and inferomedial to the intracranial optic nerve segment, respectively. On both sides, the intracranial length of the ophthalmic artery ranged from 1.5 to 4.5 mm (mean: 2.90 ± standard deviation of 0.74 mm). CONCLUSION: Awareness of the endoscopic nuances of the ophthalmic artery origin is paramount to minimize the risk of sight-threatening neurovascular injury during EEAs to the suprasellar and parasellar regions.